The Adjunctive Role of Nutritional Therapy in the Management of Phlegmon in Two Children with Crohn’s Disease - Day, Andrew S.; Brown, Stephanie C. (Frontiers in Pediatrics, 2017)
Crohn disease may be complicated by the development of penetrating (fistulising) or structuring complications. The presentation of an intra-abdominal phlegmon or abscess with or without an associated fistula has traditionally required surgical intervention. This series of two cases illustrates a beneficial role of non-surgical management, with parenteral and then enteral nutrition playing central roles. This report further elaborates the potential adjunctive role of enteral nutrition in the management of this complication of Crohn disease.